Larger Countermovement Increases the Jump Height of Countermovement Jump - Alberto Sánchez-Sixto; Andrew J. Harrison; Pablo Floría (MDPI AG, 2018)
Simulation studies show that jump performance can be improved by increasing the depth of countermovement. The purpose of this study was to determine how modifications to the depth of countermovement lead to changes in jump height and the biomechanical parameters related to center of mass displacement and force application. Twenty-nine competitive males participated in this investigation, performing nine countermovement jumps using a self-selected, a deep, and a shallow crouch position. Jump height and relative net vertical impulse were greater when using a deeper crouch position, compared to the self-selected position. Force application variables did not report differences, when the deeper countermovement was compared to the self-selected countermovement; although, the shallower countermovement showed higher values in force application parameters. The deeper countermovement jumps achieved higher velocities of the center of mass than the self-selected jumps, while shallower jumps produced lower velocities than the self-selected jumps. The results of this investigation were consistent with simulation studies, showing that deep countermovements increase net vertical impulse, leading to a higher jump height. In addition, the maximum downward velocity was higher, when the crouch position was deeper. Conversely, force-applied variables did not change when jump performance was increased.